THE RELATIONSHIP OF PARITIES AND WEIGHT WITH BABY BORN EVENT OF PERINEUM RUPTURS IN AI ARIANTI BPM: HUBUNGAN PARITAS DAN BERAT BADAN BAYI LAHIR DENGAN KEJADIAN RUPTUR PERINEUM DI BPM AI ARIANTI - Salsalina Salsalina Yuniarty G; Triswanti Triswanti (Jurnal Ilmiah Wijaya, 2018)
The background: Rupture the perineum is ripping was born. Ripping perineum occur in nearly all births, and it is not uncommon for delivery next. Ripping it can be prevented and reduced by keeping and you will pass the flanks by the head of the fetus quickly.Based on indonesia ' s demographic health survey (SDKI) in 2007, maternal mortality rate in the country reached 248 / 100,000 of life. The purpose : Prove the existence of the relation of parity and weight infants born with the rupture of the perineum in BPM Ai Arianti 2018..The methods : Methods used analytic with the approach of cross sectional.The sample collection technique by using techniques of sampling is a total of commentary on the number of deliveries totaled 40 people mother . Data collection in this research is fill a sheet observation.The result : The results of research with the use the chi square showed p-value based on the relationship of parity with the genesis of rupture the perineum of p-value 0,008 and because of pvalue 0,008 <( 0.05 ), then there is rejected meaning of this relationship parity with the rupture of the perineum, relationship based on weight infants born with the incident because of rupture of the perineum of p-value 0,005 and because of p-value 0,116> ( 0.05 ), and Ho no accepted which means there is a weight infants born with the rupture of the perineum in the BPM Ai Arianti 2018. The conclusion: there is a relationship parity and weight infants born with rupture of the perineum in the BPM Ai Arianti 2018. Advice: Expected for pregnant women to growing awareness to do gymnastics pregnant regularly can train to the perineum muscles during childbirth dan teaching how to gymnastics pregnant do the best, so it can reduce the risk of rupture of the perineum. And for the BPM Ai Ariant in the hope more can increase vigilance in doing help childbirth thus reducing the rupture of the perineum in the BPM.